Immobilization of heavy metals in ceramsite prepared using contaminated soils: Effectiveness and potential mechanisms. (January 2023) - Li, Chengming; Song, Bing; Chen, Zhiliang; Liu, Zequan; Yu, Lei; Zhi, ZeJian; Zhao, Yan; Wei, Hong; Song, Min
Abstract: Heavy metal contaminated soils pose a serious threat to the environment, and preparing ceramsite using contaminated soils was proposed as an effective method to address this threat in this study. Specifically, two typical soils (i.e., contaminated clay and sandy soil) were mixed with different ratios and calcined at temperature 1000–1200 °C to prepare ceramsite. Special attentions were paid to evaluating the immobilization of heavy metals in ceramsite and identifying the corresponding immobilization mechanisms. Using the leachability of heavy metals from ceramsite as evaluation criteria, the optimum mixing ratio of clay/sandy soil and sintering temperature were determined as 0.6:0.4 and 1200 °C. Moreover, based on the spectroscopic characterizations and thermodynamic calculation, high sintering temperature well facilitated the liquid phases formation, promoting the reactions between heavy metals and aluminosilicates and the valence state conversion of heavy metals. Accordingly, heavy metals were well immobilized in ceramsite by forming thermodynamically stable minerals, being encapsulated in solid matrix, and transforming to valence states with low mobility. The leaching conditions including pH and temperature had minimal effect on the immobilization of heavy metals in ceramsite. In summary, ceramsite prepared by contaminated soils was environmentally friendly and had good potential in engineering application as building materials. Graphical abstract: Image 1 Highlights: Co-utilization of polluted clay and sandy soil for ceramsite production is presented. The optimum ratio of clay/sandy soil and sintering temperature are 0.6:0.4 and 1200 °C. The immobilization effectiveness of heavy metals in ceramsite is evaluated. The immobilization mechanism of heavy metals in ceramsite is determined.